2014
DOI: 10.3171/2014.4.spine13319
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant human bone morphogenetic protein-2–induced ossification of the ligamentum flavum in rats and the associated global modification of histone H3

Abstract: Object The primary object of this investigation was to study recombinant human bone morphogenetic protein–2 (rhBMP-2)–induced ossification of the ligamentum flavum and associated histone H3 modification in a rat model. In an additional set of studies the authors investigated spinal cord and behavioral changes in the same model. Methods The authors report on 2 separate sets of studies. A total of 90 rats … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 30 publications
3
14
0
Order By: Relevance
“…A previous study suggested that many transcription factors, including Osterix and Runx2, play important roles in the development of OLF . We previously created a rat model using recombinant human BMP‐2‐induced OLF, and found Osterix and Runx2 expression in the fibrocartilage area of the rat ossified ligamentum flavum . Expression of Runx2 and Osterix increased similarly to that of Notch2 during the osteogenic process of ligamentum flavum cells in the present study.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…A previous study suggested that many transcription factors, including Osterix and Runx2, play important roles in the development of OLF . We previously created a rat model using recombinant human BMP‐2‐induced OLF, and found Osterix and Runx2 expression in the fibrocartilage area of the rat ossified ligamentum flavum . Expression of Runx2 and Osterix increased similarly to that of Notch2 during the osteogenic process of ligamentum flavum cells in the present study.…”
Section: Discussionsupporting
confidence: 75%
“…38 We previously created a rat model using recombinant human BMP-2-induced OLF, and found Osterix and Runx2 expression in the fibrocartilage area of the rat ossified ligamentum flavum. 39 Expression of Runx2 and Osterix increased similarly to that of Notch2 during the osteogenic process of ligamentum flavum cells in the present study. Overexpression of Notch2 significantly increased Runx2 and Osterix levels, and Notch2 knockdown produced the opposite effect.…”
Section: Notch and Olfsupporting
confidence: 72%
“…It was also reported that COL6A1 and RUNX2 may be common susceptibility genes in ligament ossification in the spine [53,54] and both of these genes have also been linked to OA [55,56]. TGFβ and BMPs are known regulators of ossification and fibrosis as well as being involved in OA development, and have also been associated with ligament ossification, including recombinant BMP2 in rat spines [57] and abnormal BMP signalling in human spines [58]. Recently, epidermal growth factor signalling was linked to OA development, comprising of ectopic chondro-osseous pathologies in the ligament and meniscus [10].…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis of spontaneous ossification of LF in vivo and the differentiation of normal and abnormal LF are still undergoing experimental research being experimentally examined. Hou et al ossified rat LF cells by embedding recombinant BMP-2 in their epidural space [ 23 ]. They found that pathological changes in ossification involved ligament degeneration, cartilage formation and, finally, bone formation.…”
Section: Discussionmentioning
confidence: 99%